Security issues in a group key establishment protocol. (5th June 2018) - Mitchell, Chris J
Abstract: Major shortcomings in a recently published group key establishment protocol are described; this protocol enables any participant to choose and broadcast a secret key to a group of other participants. We show that any valid recipient of a broadcast can successfully impersonate the originator of that broadcast to send a new key to the original set of recipients. Also, if a broadcast key is ever compromised, then any party (insider or outsider) who learns this key can force its reuse indefinitely. These shortcomings are sufficiently serious that the protocol should not be used.